Penyakit Sinosis Hepar di Hospital Kuala Lumpur 1990-1994 - Azhar M.,; Azlina A.,; Hazama M.,; Khairul S.,; Low, C.S.; Mansor R.,; Norafidah A.R,; Nuraini D., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1995)
A cross-sectional study was conducted to determine the distribution of hepatic cirrhosis by sex, age, race and signs and symptoms of hepatic cirrhosis. In this study 71 case hepatic cirrhosis from 1990 until 1994 were obtained by simple ramdom sampling from the Records Unit, Medical Faculty UKM. The data was obtained with the use of a questionnaire. The majority of the hepatic cirrhosis patient were Indians (57.8%) Chinese (20.3%) Malays (16.7%) and others race (5.0%). In this study there was significant difference in prevalence of hepatic cirrhosis among those drinking alcohol and not drinking alcohol by ethnicity (X2=22.6). There was no significant difference among hepatic cirrhosis patient thet were HbsAg positive and HbsAg negative by race (p - 0.06)